EXPLORING VISUAL SEMIOTICS IN MYKONOS MILK DROPS SERIES PERFUME PACKAGING THROUGH PIERCE’S THEORY OF NON-VERBAL SIGNS - Adlina, Nuri; Amalia, Desthia (Journal of Language and Literature, 2025)
This research aims to explore the visual semiotics of Mykonos' Milk Drops series, a collection of unisex fragrances that challenge traditional gender norms in the perfume industry. The study investigates how the packaging of these fragrances communicates the essence of the scents within, focusing on the signs and symbols employed to convey meaning and evoke consumer interest. This qualitative research employs purposive sampling to focus on three specific variants of Mykonos' Milk Drops series: Milk Drops, Pink Drops, and Café Drops. The study applies Peirce's triadic semiotic theory to examine the non-verbal signs found on the packaging, classifying them as Qualisigns, Sinsigns, Icons,  Indexes, Rheme and Dicents. This research offers valuable insights into the role of visual semiotics in the fragrance industry, particularly regarding unisex perfumes. By demonstrating how packaging can encapsulate complex ideas and emotions through visual language, the study emphasizes the significance of design in marketing strategies and its potential impact on consumer behavior. The findings contribute to a broader understanding of how brands can leverage visual communication to create meaningful connections with their audience.